STRATEGI PENGEMBANGAN PERIKANAN DI KABUPATEN ROKAN HILIR - Khaira Zakya; Zaili Rusli SD (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
This research is a Fishery Development Strategy in Rokan Hilir, this study aims to find out an effective and efficient Fisheries Strategy based on human resources, natural resources and lack of budget to make supporters and obstacles in determining the strategy of Fisheries Department, this research using SWOT analysis method is strength, weakness, opportunities, threats.Based on the results of research shows that the Government's policy has not been run in accordance with the Government's expectation in increasing the number of fishery production as well as restore Bagansiapiapi glorious period in fish production. Constraints faced in the development of fisheries strategy are the problems in the implementation of fishery development of Rokan Hilir Regency, namely the low level of income of traditional fishermen, the low quality of fishery products production, the low institutional capacity and the human resources (fishermen) and fish farmers, Potential of cultivation, lack of optimal management of Fish Seed Meal (FSM), damage to coastal ecosystem (mangrove) in some areas, limited fishery production facilities and infrastructure for fishermen, limited access of goods transport to fishery production centers and decreasing of fish catch resources.The theory used by the authors in this study is the theory of Rangkuti (2006) that explains about the SWOT analysis of SO strategy, this strategy is made based on the way of thinking utilizing all the power to seize and take advantage of opportunities as much as possible. Strategy st, this strategy is a strategy in using the power that has to overcome the threat. Strategy wo, this strategy is applied based on the utilization of existing opportunities by minimizing existing weaknesses. WT Strategy, This strategy is based on business activities to minimize existing weaknesses and avoid threats.From the results of the research, Rokan Hilir fisheries development strategy found barriers in determining what strategies will be determined in accordance with the factors faced by the Fisheries Department, but the Fisheries Department has been working hard to provide increased production of fisheries, with SWOT analysis guidelines certainly make it easier to understand will The conditions faced today in order to achieve the Government's goal to promote and restore the glory of Bagansiapiapi.Keywords: Development Strategy, Rokan Hilir Fishery.